Koumine Decreases Astrocyte-Mediated Neuroinflammation and Enhances Autophagy, Contributing to Neuropathic Pain From Chronic Constriction Injury in Rats - Jin, Gui-lin; Yue, Rong-cai; He, Sai-di; Hong, Li-mian; Xu, Ying; Yu, Chang-xi (Frontiers in Pharmacology, 2018)
Koumine, an indole alkaloid, is a major bioactive component of Gelsemium elegans. Previous studies have demonstrated that koumine has noticeable anti-inflammatory and analgesic effects in inflammatory and neuropathic pain (NP) models, but the mechanisms involved are not well understood. This study was designed to explore the analgesic effect of koumine on chronic constriction injury (CCI)-induced NP in rats and the underlying mechanisms, including astrocyte autophagy and apoptosis in the spinal cord. Rats with CCI-induced NP were used to evaluate the analgesic and anti-inflammatory effects of koumine. Lipopolysaccharide (LPS)-induced inflammation in rat primary astrocytes was also used to evaluate the anti-inflammatory effect of koumine. We found that repeated treatment with koumine significantly reduced and inhibited CCI-evoked astrocyte activation as well as the levels of pro-inflammatory cytokines. Meanwhile, we found that koumine promoted autophagy in the spinal cord of CCI rats, as reflected by decreases in the LC3-II/I ratio and P62 expression. Double immunofluorescence staining showed a high level of colocalization between LC3 and GFAP-positive glia cells, which could be decreased by koumine. Intrathecal injection of an autophagy inhibitor (chloroquine) reversed the analgesic effect of koumine, as well as the inhibitory effect of koumine on astrocyte activation in the spinal cord. In addition, TUNEL staining suggested that CCI-induced apoptosis was inhibited by koumine, and this inhibition could be abolished by chloroquine. Western blot analysis revealed that koumine signiﬁcantly increased the level of Bcl-xl while inhibiting Bax expression and decreasing cleaved caspase-3. In addition, we found that koumine could decrease astrocyte-mediated neuroinflammation and enhance autophagy in primary cultured astrocytes. These results suggest that the analgesic effects of koumine on CCI-induced NP may involve inhibition of astrocyte activation and pro-inflammatory cytokine release, which may relate to the promotion of astrocyte autophagy and the inhibition fo apoptosis in the spinal cord.